Crack Size and Undermatching Effects on Fracture Behavior of a Welded Joint - Sedmak, Aleksandar; Doncheva, Elisaveta; Medjo, Bojan; Rakin, Marko; Milosevic, Nenad; Radu, Dorin (MDPI Materials (Basel, Switzerland), 2023)
Crack size and undermatching effects on fracture behavior of undermatched welded joints are presented and analyzed. Experimental and numerical analysis of the fracture behavior of high strength low-alloyed (HSLA) steel welded joints with so-called small and large crack in undermatched weld metal and the base metal was performed, as a part of more extensive research previously conducted. J integral was determined by direct measurement using special instrumentation including strain gauges and a CMOD measuring device. Numerical analysis was performed by 3D finite element method (FEM) with different tensile properties in BM and WM. Results of J-CMOD curves evaluation for SUMITEN SM 80P HSLA steel and its weld metal (WM) are presented and analyzed for small and large cracks in tensile panels. This paper is focused on some new numerical results and observations on crack tip fields and constraint effects of undermatching and crack size keeping in mind previously performed experiments on the full-scale prototype. In this way, a unique combined approach of experimental investigation on the full-scale proto-type and tensile panels, as well as numerical investigation on mismatching and crack size effects, is achieved.
Keywords: welded joint mismatching; crack tip fields; finite element method